Risk factors that provoke development of the digestive pathology and psoriasis - A. S. Salikhova; A. Ya. Kryukova; Z. R. Khismatullina; A. A. Ibliyaminova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2013)
The paper deals with the risk factors that provoke aggravation of psoriasis, with special attention to the stress the patient experiences among coworkers. Careful examination of the digestive system organs has shown that in case of their pathology and in case of psoriasis there are similar risk factors – the fact to be taken into account in complex management of such patients.